Desenvolvimento e implementação do sistema mecânico de um protótipo de bomba de infusão de insulina de baixo custo - Tenorio, Fernanda Silva [UNIFESP] (2019)
Introduction: Diabetes mellitus is a worldwide epidemic, and according to the World Health Organization, 14 million people live with the disease in Brazil. Diabetes Mellitus is one of the four major types of noncommunicable diseases, characterized by chronic hyperglycemia due to failure in insulin secretion, action, or both. Uncontrolled blood glucose increases the risk for the development of chronic severe complications, including nephropathy, neuropathy, retinopathy, and cardiomyopathy. Among the available treatments and technologies for diabetes mellitus management, the use of continuous insulin infusion pump has been shown to improve glycemic control of diabetic patients, reduce severe hyperglycemia and the number of hospitalizations due to ketoacidosis, compared to conventional treatment. Although the benefits from the use of continuous insulin infusion pump are expressive, and approximately 15% of type 1 diabetics have an absolute indication for its use, the number of patients with access to this treatment is still very low, especially in Brazil. The main limiting factor for the use of continuous insulin infusion pump refers to the high cost of the device and supplies since these are imported items. Considering the high costs and limited use of the device in Brazil and developing countries, our research group has been working on the development of a low-cost continuous insulin infusion pump prototype during the last five years, and whose estimated value would represent one-quarter of value of commercially available equipment. Objective: This study aimed to develop a miniaturized mechanical system for a low-cost insulin infusion pump, seeking to approximate the prototype of a functional, reliable and viable product for the market. Methods: A miniaturized mechanical system was developed using computer-aided engineering technology, computer-assisted design tools, and finite element methodology. The prototype was developed and integrated into the microelectronic system (already developed by our group in a previous project), enabling the execution of in vitro functional tests to assess the accuracy and reliability of the device. Results: The low-cost prototype coupled with the developed miniaturized mechanical system resulted in a compact and functional device, with good accuracy and potential to become a commercial product. The present study demonstrated that the prototype infused the programmed fluid doses with an average error of -2.2%. Also, the percentage of infusions that were within ± 5% accuracy was 42.50% and of 84.17% for the ± 15% limit. Conclusions: The developed miniaturized mechanical system presented functionality, precision, and accuracy and, when coupled to the electronic system, responded well to repeatability tests. Additionally, the results from the in vitro tests demonstrated that the performance of the device is satisfactory and comparable to commercial continuous insulin infusion pumps. Although new experiments will be necessary to improve and adjust the evaluation methodology and the device, this study presents this low-cost prototype as a candidate to be used by type 1 diabetic patients in Brazil and developing countries, especially in the context of public health.